Functional Antagonism of WRI1 and TCP20 Modulates GH3.3 Expression to Maintain Auxin Homeostasis in Roots - Que Kong; Pui Man Low; Audrey R. Q. Lim; Yuzhou Yang; Ling Yuan; Wei Ma (Plants, 2022)
Auxin is a well-studied phytohormone, vital for diverse plant developmental processes. The GH3 genes are one of the major auxin responsive genes, whose expression changes lead to modulation of plant development and auxin homeostasis. However, the transcriptional regulation of these GH3 genes remains largely unknown. WRI1 is an essential transcriptional regulator governing plant fatty acid biosynthesis. Recently, we identified that the expression of GH3.3 is increased in the roots of wri1-1 mutant. Nevertheless, in this study we found that AtWRI1 did not activate or repress the promoter of GH3.3 (proGH3.3) despite of its binding to proGH3.3. Cross-family transcription factor interactions play pivotal roles in plant gene regulatory networks. To explore the molecular mechanism by which WRI1 controls GH3.3 expression, we screened an Arabidopsis transcription factor library and identified TCP20 as a novel AtWRI1-interacting regulator. The interaction between AtWRI1 and TCP20 was further verified by several approaches. Importantly, we found that TCP20 directly regulates GH3.3 expression via binding to TCP binding element. Furthermore, AtWRI1 repressed the TCP20-mediated transactivation of proGH3.3. EMSAs demonstrated that AtWRI1 antagonized TCP20 from binding to proGH3.3. Collectively, we provide new insights that WRI1 attenuates GH3.3 expression through interaction with TCP20, highlighting a new mechanism that contributes to fine-tuning auxin homeostasis.